(untitled) (American Journal of IR 4.0 and Beyond, 2024)
The dispatch of practical instructions to schools and supervisors prior to the actual conduct of the practical examination over the years has not received the same level of attention as that given to the movements of people and goods and, therefore, is prone to challenges. However, the process could be automated using artificial intelligence. Previous studies have investigated the effects of automation on the control and delivery of goods in the transport management sector, mostly in the Western world. Therefore, this study assessed science teachers’ challenges and readiness for artificial intelligence in practical instruction control and delivery systems. The study adopted ex-post facto design and used one hundred science teachers as participants. Science Teacher Readiness for Automated Practical Instruction Control and Delivery (r = 0.83) was used to collect data. The data collected were analysed descriptively. There are more male (73%) science teachers than female (27%). 84% of the respondent listed cost as one of the challenges, and 83% of the respondents indicated resistant to change and technical difficulties, ethical issue 67% and integration with existing system 65%) 64 The science teachers are moderately ready 64% while 24% are lowly ready and 12% are highly ready for the deployment of automated practical instruction control and delivery system. Artificial intelligence for science practical instruction delivery has greater benefits than the manual way of delivery; however, science teachers are ready for its deployment despite its challenges. Therefore, efforts should be geared towards overcoming the inherent challenges so that the benefits can be fully enjoyed.